Ecotoxicological effects of manganese-zinc ethylenebis (dithiocarbamate) on terrestrial Oligochaeta : extrapolating from laboratory to field - Vermeulen, Laura Anne (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1996.